Job Creation : Why Some Countries Do Better - Garibaldi, Pietro (Economic Issues; Economic Issues ;, 2000)
Over the past decade, the United States has been very successful atcreating jobs. Some other industrial countries have clearly lagged behind. But what is the reason why some countries are more successful than others at creating employment? Are there common factors that explainjob creation? This paper presents the findings of a new IMF study that has systematically analyzed job creation over the past two decades in theindustrial countries, focusing particularly on differences within Europe.